Genome-wide identification and characterization of genes involved in melatonin biosynthesis in Morus notabilis (wild mulberry). (September 2021) - Zheng, Sha; Zhu, Yingxue; Liu, Changying; Fan, Wei; Xiang, Zhonghuai; Zhao, Aichun
Abstract: Melatonin is recognized as an important regulator for human health and widely distributed in many plant species, including mulberry ( Morus L.). Previous studies suggested mulberry contains high melatonin content, but the molecular mechanisms underlying melatonin biosynthesis in mulberry remain unclear. Here, 37 genes involved in melatonin biosynthesis were identified in mulberry genome, including a tryptophan decarboxylase gene ( MnTDC ), seven tryptophan 5-hydroxylase genes ( MnT5H s), six serotonin N-acetyltransferase genes ( MnSNAT s), 20 N-acetylserotonin methyltransferase genes ( MnASMT s) and three caffeic acid 3-O-methyltransferase genes ( MnCOMT s). Expression analysis showed that MnTDC, MnT5H2, MnSNAT5, MnASMT12 and MnCOMT1 from these genes had highest expression levels within their corresponding families. In vitro enzymatic assays indicated that MnTDC, MnT5H2, MnSNAT5, MnASMT12 and MnCOMT1 play important roles in melatonin biosynthesis. Multiple different pathways for melatonin biosynthesis in mulberry were discovered. In addition, mulberry ASMT showed distinct roles with those of ASTMs in Arabidopsis and rice. The class I ASMT, MnASMT12, and the class III ASMT, MnASMT20, catalyzed the conversion of N-acetylserotonin to melatonin and serotonin to 5-methoxytryptamine. Furthermore, the class II ASMT, MnASMT16, only catalyzed the conversion of N-acetylserotonin to melatonin. This study improved our knowledge on melatonin biosynthesis in mulberry and expands the repertoire of melatonin biosynthesis pathways in plants. Graphical abstract: Image 1 Highlights: In total 37 genes involved in melatonin biosynthesis were identified in Morus notabilis for the first time. Expression patterns of the 37 melatonin biosynthetic genes in different tissues were revealed. Multiple pathways efficiently catalyze tryptophan to melatonin in mulberry. The role of different classes of the ASMT family in mulberry was firstly conducted.